Horizontal seismic wave at ground surface from transfer function based on ambient noise - Lim, Doyoon; Ahn, Jae-Kwang (Frontiers in Earth Science, 2023)
Earthquake detection can be improved by ensuring that seismometer sites experience little artificial noise in the surrounding environment. To minimize noise, seismological observatories should be positioned in rocky mountainous areas without nearby valleys, away from significant human activity. However, such surface sites may be scarce when constructing dense monitoring networks, thereby necessitating the use of underground sites to ensure low noise levels. The Korean Meteorological Administration (KMA) is currently installing new underground seismometers to increase seismic monitoring capacity. However, seismic data on the ground surface are also required for engineering technological developments (to reduce damage to structural components). Therefore, borehole seismic stations without surface seismometers need to estimate ground surface motion from borehole record data. We propose a transfer function that converts motion within boreholes to surface seismic waves using ambient noise, thereby facilitating estimation of ground surface motions using borehole seismometers. As a result, a ground surface motion prediction was possible from borehole record data. Since the proposed method could simulate only to linear amplification of the target site, it is suitable for light to moderate earthquakes or/and sites of long epicenter distance.